Influence of crystal orientation on the corrosion behaviour of copper, aluminium and niobium studied using first-principles calculation - Yang, Jun (2023)
Corrosion has an important impact on the properties of metal materials. Copper (Cu), aluminum (Al) and niobium (Nb) are widely used in many important fields because of their excellent properties. However, all the three metals are prone to corrosion. In study, the corrosion behaviour of Cu and Al were systematically studied by experimental methods, and the corrosion mechanisms were analyzed by First-principles Calculation. Subsequently, the results of Cu and Al obtained were employed to predict the corrosion resistance of Nb films with different crystal orientations. Firstly, the electrochemical method was used to illustrate the corrosion resistance of Cu and Al with (100), (110) and (111) surfaces in 3.5wt% NaCl, 0.1M H2SO4 and 0.1M NaOH solution, respectively. Both the electrochemical impedance spectroscopy (EIS) and polarization curve results revealed that crystal orientation has significant effect to the corrosion resistance of Cu and Al. The order of corrosion resistance for copper was Cu(110) > Cu(100) > Cu(111), and for aluminium was Al(100) > Al(110) > Al(111). Moreover, the corrosion resistance sequence of Cu and Al was the same in 3.5wt% NaCl, 0.1M H2SO4, and 0.1M NaOH solution, suggesting that the solution type has no impact on the crystal orientation affecting the corrosion resistance of Cu and Al. Secondly, the surface energy, work function, Mulliken charge population analysis and vacancy formation energy were calculated through First-principles calculation to reveal the corrosion mechanism. The calculation results showed that the Mulliken charge distribution was closely related to the corrosion resistance. A higher value of Mulliken charge led to a greater number of electrons participating in the electrochemical reaction, which in turn resulted in a poorer corrosion resistance. The electron number on each atom on Cu(100), Cu(110), Cu(111) plane was 11.04 e, 10.94 e and 11.14 e, respectively. And the values of Al(100), Al(110), Al(111) was 2.96 e, 2.91 e and 2.99 e, respectively. The Mulliken value order was (111) > (100) > (110), indicating the corrosion resistance sequence was (110)> (100)> (111) for both Cu and Al. In addition, due to the vacancy effect of Al, the vacancy formation energy of Cu(100), Cu(110), Cu(111) were 6.76 eV, 6.71 eV and 7.38 eV, respectively. While the values of Al(100), Al(110), Al(111) were 5.11 eV, 4.63 eV and 5.32 eV, respectively. It indicated that the vacancy was easier to form on the surface of Al than Cu. In the early stage of corrosion process, the corrosion resistance was Al(110)> Al(100) >Al(111), which was controlled by surface effect. In the late period, the corrosion resistance order changed to Al(100)> Al(110) >Al(111), which controlled by surface effect and vacancy effect. To predict the corrosion resistance of Nb with (100), (112), (110) and (120) planes, the surface energy, work function, Mulliken charge population analysis and vacancy formation energy were also calculated through First-principles calculation. Based on the analysis results of Cu and Al, the Mulliken charge distribution was used to predict the corrosion resistance of Nb. Results showed the values of Mulliken charge on the surface atom for the four structures were 13.18 e, 13.13 e, 13.19 e and 13.21 e. Therefore, the order of corrosion resistance for niobium will be Nb(112) > Nb(100) > Nb(110) > Nb(120). This study implies that the First-principles calculation by Mulliken charge analysis and vacancy formation energy analysis can be used to explain the corrosion mechanism metals in different solutions. Moreover, metal-corrosion data can be used to explain the important development trend of metals through simulation approach.